Geology of the southern part of Sabanalarga Batholith. Implications for terrane theory in the west of Colombia (2015)
The Colombian Andes are the product of the interaction of terranes with different geological affinity, such as the Western Cordillera, which is made up of blocks of oceanic affinity, that have been accreted to the western boundary of pre-existing terranes with continental affinity. The study area is geologically dominated by the Sabanalarga Batholith, which has at least two facies, gabro-diorite and tonalitiegranodiorite, that intrude the Barroso Formation. Both units have been affected strongly by regional faults generating large areas of mylonites closely related with hydrothermal alterations and mineralization occurrences. Due the clear intrusive relationship between the Sabanalarga Batholith and Barroso Formation, and due the Cauca-Almaguer fault cuts both units without separating them, it is suggested that the Terranes Theory must be reconsidered in this part of the country, because the Cauca-Almaguer fault do not correspond to the boundary between Calima Terrane and the terranes Arquía and Quebradagrande.